On the Lexical Integrity Hypothesis and its (In)accurate Predictions - Bosque, Ignacio (IBERIA: An International Journal of Theoretical Linguistics, 2014)
The Lexical Integrity Hypothesis (LIH) holds that lexical items are syntactic atoms, which implies that neither their segments nor their semantic components are accessible to syntax. LIH is, thus, a double-faced hypothesis, since its predictions are relevant for both the syntax-lexicon interface and the morphology-syntax distinction, and specifically the controversial issue of whether or not morphology is an independent component of the Grammar. Both sides of LIH are addressed in this paper through a series of syntactic tests (movement, scope, modification, anaphora, ellipsis, coordination), which are shown to often give different results depending on whether the grammatical units targeted are semantic components (and lack phonological features) or morphological segments. LIH is shown to be only partially wrong. Its failures, which cannot be dismissed, are shown not to be random, since, to a large extend, they depend on the grammatical properties of the relevant components of lexical items.